2016
DOI: 10.4049/jimmunol.1502291
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Restrain Spontaneous Antitumor CD8+ T Cell Priming through PD-1/PD-L1 Interactions with Dendritic Cells

Abstract: Despite the classical function of NK cells in the elimination of tumor and of virus-infected cells, evidence for a regulatory role for NK cells has been emerging in different models of autoimmunity, transplantation, and viral infections. However, this role has not been fully explored in the context of a growing tumor. In this article, we show that NK cells can limit spontaneous cross-priming of tumor Ag-specific CD8+ T cells, leading to reduced memory responses. After challenge with MC57 cells transduced to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 53 publications
3
77
0
Order By: Relevance
“…However, it is still unclear whether the effects of PD‐L1 and PD‐L2 on PD‐1 downstream signaling are dependent on the cell type that expresses the ligand. A recent study suggested that PD‐L1 expressing murine NK cells can suppress DC maturation and activation, while having no direct effect on T‐cell activation . To our knowledge, this is the first report to suggest that not all PD‐L1 expressing cell types are capable of directly inhibiting T cells through PD‐1 ligation.…”
Section: Immune Checkpoints Control Effector T‐cell and Nk‐cell Respomentioning
confidence: 76%
“…However, it is still unclear whether the effects of PD‐L1 and PD‐L2 on PD‐1 downstream signaling are dependent on the cell type that expresses the ligand. A recent study suggested that PD‐L1 expressing murine NK cells can suppress DC maturation and activation, while having no direct effect on T‐cell activation . To our knowledge, this is the first report to suggest that not all PD‐L1 expressing cell types are capable of directly inhibiting T cells through PD‐1 ligation.…”
Section: Immune Checkpoints Control Effector T‐cell and Nk‐cell Respomentioning
confidence: 76%
“…15 When NK cells were reduced, there was an increase in CD8 1 tumor-directed effector cells. Furthermore, when primed in the absence of NK cells, this population of CD8 1 effector T cells protected against tumor growth and formation of secondary tumors in mice that were rechallenged.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when primed in the absence of NK cells, this population of CD8 1 effector T cells protected against tumor growth and formation of secondary tumors in mice that were rechallenged. 15 Given this new regulatory function, the reduction of NK cells that occurs during daratumumab treatment may enhance the antitumor immune response. An increase in CD8 1 effector memory T cells was observed in patients treated with single-agent daratumumab.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells have been reported to contribute to tumor control in some settings [82], but in established B16 tumors NK cells also have been shown to have regulatory function resulting in immune suppression, in part through PD-L1 expression [83]. Similarly, γδT cells are capable of direct tumor recognition and in some circumstances can be activated to kill tumor cells, but at the same time γδT cells with regulatory function have been identified from human breast cancer tissues [84].…”
Section: Potential Role For Additional Innate Immune Sensorsmentioning
confidence: 99%